MEAMfit: A reference-free modified embedded atom method (RF-MEAM) energy and force-fitting code - Duff, Andrew Ian; Finnis, M.W.; Maugis, Philippe; Thijsse, Barend J.; Sluiter, Marcel H.F. (Computer physics communications, 2015)
Ab initio modeling of materials has become routine in recent years, largely due to the success of density functional theory (DFT). However, for many processes in materials, realism is achieved only when millions of atoms are considered. Currently, such large scale simulations are beyond ab initio capabilities so that one has to resort to effective interatomic potentials that well represent ab initio data on smaller scales. Two of the more widely used types of interatomic potentials are embedded atom method (EAM) and modified embedded atom method (MEAM) potentials. Here we present a code that can use ab initio generated energies and forces to obtain representative EAM and reference-free MEAM type effective interatomic potentials. We illustrate the use of this code with ab initio computed thermal excitations in ZrC. Program title: MEAMfit Catalogue identifier: AEWY_v1_0 Program summary URL:http://cpc.cs.qub.ac.uk/summaries/AEWY_v1_0.html Program obtainable from: CPC Program Library, Queen’s University, Belfast, N. Ireland Licensing provisions: Standard CPC licence, http://cpc.cs.qub.ac.uk/licence/licence.html No. of lines in distributed program, including test data, etc.: 4467841 No. of bytes in distributed program, including test data, etc.: 56403685 Distribution format: tar.gz Programming language: Fortran. Computer: Linux based workstations. Operating system: Linux. RAM: 120 Megabytes Classification: 16.1. External routines: TOMS611 Unconstrained Minimization [1] included in the MEAMfit code. Nature of problem: Fitting embedded atom method (EAM) and reference-free modified embedded atom method (RF-MEAM) potentials [2-3] to energies and forces produced by VASP [4-7]. Solution method: A computer program is presented which uses a conjugate-gradient minimizer paired with a genetic algorithm to fit EAM and RF-MEAM potentials to energies and/or atomic forces read directly from VASP output files. Potentials produced by the code are directly usable with the LAMMPS [8] or Camelion [9] molecular-dynamics packages. Additional comments: User manual provided. !!! The distribution file for this program is over 56 Mbytes and therefore is not delivered directly when download or Email is requested. Instead a html file giving details of how the program can be obtained is sent. !!! Running time: The run-time depends on the required level of accuracy of the final potential. For an EAM potential fit to 670 energies, a few hours on a single core is usually sufficient to produce a potential with R=12%–13% (see Equation. 9 in main-text for definition). To ensure a maximally optimized potential however (R=12%), a run-time of 24 hours is recommended. To optimize a RF-MEAM potential, a further 24 hours should be allowed. One will already find an improvement over the EAM using just a single core, however to ensure a maximally optimized potential, one should run several instances of MEAMfit in parallel. References:[1]J. E. Dennis, D. Gay and R. E. Welsch, ACM Trans. on Math. Soft., 7 (1981) 348-368.[2]M. I. Baskes, Materials Science and Engineering A, 261 (1999), 165.[3]M. Timonova and B. J. Thijsse, Modelling Simul. Mater. Sci. Eng., 19 (2011) 015003.[4]G. Kresse, J. Hafner, Phys. Rev. B 47 (1993) 558.[5]G. Kresse, J. Hafner, Phys. Rev. B 49 (1994) 14251.[6]G. Kresse, J. Furthmüller, Comput. Mat. Sci. 6 (1996) 15.[7]G. Kresse, J. Furthmüller, Phys. Rev. B 54 (1996) 11169.[8]S. Plimpton, J. Comp. Phys. 117 (1995) 1–19.[9]http://tinyurl.com/camelion11-53.